Combination of non-ablative fractional photothermolysis and 0.1% tacrolimus ointment is efficacious for treating idiopathic guttate hypomelanosis. (2nd September 2016) - Chitvanich, Sarinya; Rerknimitr, Pawinee; Panchaprateep, Ratchathorn; Pongprutthipan, Marisa; Asawanonda, Pravit
Abstract: Background : The efficacy of fractional photothermolysis and topical use of calcineurin inhibitors as treatments of idiopathic guttate hypomelanosis (IGH) have been reported. Data on combination treatments are lacking. Objectives : To evaluate the efficacy and safety of 1550-nm ytterbium/erbium fiber laser combined with 0.1% tacrolimus ointment as a treatment of IGH. Methods : In each patient with IGH, two lesions were assigned as a treatment group, whilst two lesions on another side were chosen as control. Four treatments by fractional 1550-nm ytterbium/erbium fiber laser were delivered every four weeks combined with a twice daily topical application of 0.1% tacrolimus ointment. Lesional skin color was measured by colorimeter. Digital and dermoscopic digital photographs were taken and evaluated by three dermatologists. Results : A total of 120 lesions were treated. Combination treatment normalized the relative lightness index of IGH which reached statistical significant compared with the control at week 12, after three sessions of laser treatment ( p  = 0.026). Physicians' assessment score revealed that 91.67% of the lesions on treatment side showed an improvement. Swelling and redness were the most common side effects which spontaneously resolved. Conclusion : Fractional 1550-nm ytterbium/erbium fiber laser combined with topical 0.1% tacrolimus ointment was effective for IGH.